Prevalence of hypertension and its associated risk factors in young adults attending a tertiary care institute of Nagpur: a cross sectional study - Patil, Chaitanya R.; Sahoo, Durgesh Prasad; Dhoble, Manjusha; Kherde, Abhijit; Inamdar, Asim (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is a silent killer and global public health problem. With the advent of globalization affecting the lifestyle of the population, non-communicable diseases like hypertension, diabetes etc. is affecting the young adults (18 to 40 years). The aim of the study was to estimate the prevalence of hypertension and its associated risk factors among young adults (18 to 40 years) attending a tertiary care centre of Nagpur. Methods: This was a cross sectional study on 370 participants of age 18 to 40 years attending the outpatient department of urban health training centre in Nagpur. Data was collected using pretested and pre designed questionnaire and anthropometric measurements were done by standard guidelines. Blood pressure was measured using sphygmomanometer in sitting position. Data was analyzed using Epi info version 7.2. Chi square test/ fisher’s exact test has been used to find the difference between two proportions. Unadjusted odds ratio was calculated for various risk factors studied. Stepwise logistic regression analysis was done to calculate the adjusted odds ratio. Results: The prevalence of hypertension was found to be 23.24%. The prevalence was higher among males (25%) when compared to females (22.3%). Body mass index and waist hip ratio were significantly higher among the hypertensive when compared to normotensive study population (p<0.01). For every one year increase in age, the odds ratio increases by 1.06 (1.02 to 1.09) and the subjects who were overweight were having 2.15 odds of being hypertensive. Conclusions: We found a high prevalence of hypertension among the adults of age group of 18 to 40 years. The population with high body mass index, high waist to hip ratio and age group of 30 to 40 years were found to be associated with hypertension. Early surveillance and prompt treatment forms will help in decreasing the cardiovascular risk of young adults in near future.